Hybrid governance and performances of environmental accounting. (15th April 2021) - Ghosh, Ritwick; Wolf, Steven
Abstract: Multiple centers of authority in hybrid forms create conditions of radical openness where questions of value and fitness are in flux. Environmental accounting is suggested as a condition for steadying hybrid forms and opening up possibilities for institutional innovations. This paper advances a critical social science analysis of environmental accounting to help specify how, when, and in what ways strengthening accounting capacity advances hybrid governance. Social studies of accounting argue that accounting systems are contingent on institutions: rules and social conventions, not only data or science. Our practice-centered analysis of two cases of building environmental accounting tools to advance high profile institutional innovations in US agri-environmental governance finds that the systems of rules that structure and legitimize accounting protocols are not pre-given. The same radical openness that presents opportunities for hybridity also reinforces uncertainties in building accounting standards. We identify two major frictions: a) Conventions for determining technical consensus and b) Rules for determining levels of transaction costs. We conclude by identifying a need to think about hybrid forms critically. Although hybrid forms are an expression of creativity and collaboration, they are also performances of a certain contemporary political covenant that delegitimizes state-centered governance. The challenge ahead is to understand when and where hybrid arrangements add to socio-ecological regulation and where they undermine the possibility of more functional approaches through a performance of seriousness. Highlights: Environmental accounting as an increasingly visible element of environmental governance. Rules to establish and legitimize accounting protocols are not pre-given. Performing accounting routines carries symbolic weight. Environmental accounting can be a vehicle for "sustaining the unsustainable".